Prognostic Factors for Immune Thrombocytopenia Outcome in Greek Children: A Retrospective Single-Centered Analysis - Alexandros Makis; Athanasios Gkoutsias; Theodoros Palianopoulos; Eleni Pappa; Evangelia Papapetrou; Christina Tsaousi; Eleftheria Hatzimichael; Nikolaos Chaliasos (Advances in Hematology)
Immune thrombocytopenia (ITP) in children has a varied course and according to duration is distinguished as newly diagnosed (<3 months), persistent (3–12), and chronic (>12) types. Several studies have evaluated the prognostic factors for the progression of the disease, but similar works have yet to be performed in Greece. We aimed to identify prognostic markers for the three forms of the disease in 57 Greek children during a 13-year period. Information regarding age, gender, preceding infection, bleeding type, duration of symptoms and platelets at diagnosis, treatment, disease course, and immunological markers was recorded. 39 children had newly diagnosed, 4 persistent, and 14 chronic disease. Chronic ITP children were more likely to be of age > 10 years (p=0.015) and have gradual initiation of the disease (p=0.001), platelets > 10 × 109/L (p=0.01), and impaired immunological markers (p<0.003) compared to newly diagnosed/persistent groups. Recent history of infection was found mainly in the newly diagnosed/persistent group (p=0.013). None of the children exhibited severe spontaneous bleeding. Conclusion. Even though ITP in children usually has a self-limited course, with rare serious bleeding complications, the chronic form of the disease is characterized by different predictive parameters, which can be used in clinical practice.